CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF THE CRIMINAL ACT OF FORGERY OF COVID-19 CERTIFICATES (Study of Bitung District Court Decision Number 141/Pid.B/2021/PN Bit) - Mayang Sari; Dahlan; Bambang Fitrianto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The crime of forgery is a crime that contains elements of untruth or falsehood of an object that appears from the outside as if it is true, when in fact it is contrary to the real thing. This study aims to examine and analyze legal arrangements regarding the alleged forgery of Covid 19 swab certificates according to laws in Indonesia, the legal consequences committed by perpetrators of crimes related to the forgery of Covid 19 swab certificates and legal liability for perpetrators of the crime of forging Covid 19 swab certificates based on the decision of the Bitung district court Number 141/Pid.B/2021/PN Bit. This research method uses a type of normative juridical research that is descriptive analytical. The data sources obtained using secondary data are based on primary and secondary legal materials. The data collection technique used is a literature study. Legal arrangements related to alleged forgery of letters, especially doctors' certificates in Indonesia, have been regulated in the Criminal Code, especially Articles 267 and 268. Bitung District Court Decision Number 141/PID. B/2021/PN Bit emphasized that the application of criminal sanctions for falsifying Covid 19 swab certificates is a criminal conviction contained in the Criminal Code, namely article 268. The application of strict and definite punishment is urgently needed to prevent criminal behavior and provide a deterrent effect for other individuals who have the potential to commit similar acts.